2022
DOI: 10.3390/en15197130
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy Alloys for Energy Conversion and Storage: A Review of Grain Boundary Wetting Phenomena

Abstract: The multicomponent alloys with nearly equal concentration of components, also known as high entropy alloys (HEAs), were first proposed 22 years ago. The HEAs quickly became very important in materials science due to their unique properties. Nowadays, the HEAs are frequently used in energy conversion and storage applications. HEAs can consist of five, six or more components. Plasma cladding permits coating of the large surfaces of cheap substrates with (often expensive) HEAs and to enlarge, in such a way, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…However, different coating preparation methods led to some variations in phase structures and microstructures of HEAs. 14,15 Presently, the main methods for preparing HEACs included thermal spray, 16 electrochemical deposition, 17 magnetron sputtering, 18 laser cladding, 19 and plasma spraying. 20 Dang et al 21 prepared CoCrFeNiMn HEAC films by high vacuum radio frequency (RF) magnetron sputtering technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, different coating preparation methods led to some variations in phase structures and microstructures of HEAs. 14,15 Presently, the main methods for preparing HEACs included thermal spray, 16 electrochemical deposition, 17 magnetron sputtering, 18 laser cladding, 19 and plasma spraying. 20 Dang et al 21 prepared CoCrFeNiMn HEAC films by high vacuum radio frequency (RF) magnetron sputtering technique.…”
Section: Introductionmentioning
confidence: 99%
“…The TiZrHfMoCrCo alloy studied in this paper belongs to promising biomaterials, its biocompatibility is comparable to commercially pure titanium, which is used for orthopedic implants. Detailed reviews on HEAs can be found in References [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the high-entropy alloys (HEAs) were originally proposed by Cantor et al [1] and Yeh et al [2], there has been a growing interest in these multicomponent metallic materials. With a wide range of chemical compositions available, HEAs exhibit a variety of phase transformations, mechanical properties, and microstructural types, leading to a wealth of research publications, including numerous reviews [3][4][5][6]. Typically, HEAs consist of five or more components, with proportions ranging from 5 to 35 at.%.…”
Section: Introductionmentioning
confidence: 99%